2019
DOI: 10.3390/molecules24203720
|View full text |Cite
|
Sign up to set email alerts
|

A New Alkylation of Aryl Alcohols by Boron Trifluoride Etherate

Abstract: The ethylation of aryl alcohols by an ethyl moiety of boron trifluoride etherate is described. The reaction proceeded cleanly and afforded good yields of the corresponding aryl ethyl ethers. It tolerated the presence of functional groups such as aryl, alkyl, halogens, nitro, nitrile, and amino. However, the presence of amino or nitro groups ortho to a hydroxyl group of an aryl compound drastically reduced the yields of the anticipated products due to the chelation of the aforementioned functional groups with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Previously, Coyle et al , have reported the use of BF 3 OEt 2 for phenolic alkylation . It has been recently reported that BF 3 OEt 2 promotes the formation of carbocation with aliphatic −OH groups by coordination of the oxygen atom, followed by the transfer of the alkyl moiety. , Thus, a possibility of activation of aliphatic −OH in methoxyethanol by BF 3 OEt 2 exists. Simultaneously, Lewis acid BF 3 OEt 2 can also deactivate the pyrimidinone ring by preventing keto→enol conversion, secondary to its interaction with −NH group.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Coyle et al , have reported the use of BF 3 OEt 2 for phenolic alkylation . It has been recently reported that BF 3 OEt 2 promotes the formation of carbocation with aliphatic −OH groups by coordination of the oxygen atom, followed by the transfer of the alkyl moiety. , Thus, a possibility of activation of aliphatic −OH in methoxyethanol by BF 3 OEt 2 exists. Simultaneously, Lewis acid BF 3 OEt 2 can also deactivate the pyrimidinone ring by preventing keto→enol conversion, secondary to its interaction with −NH group.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding those monosubstituted species containing third-period elements, we obtain the following trends in BDEs (included in parentheses and expressed in kJ mol −1 ): AlH 2 (637.5) < PH 2 (685.2) < SiH 3 (686.6) < SH (687.3) < Cl (708.3). It is of interest to note that, apart from comparing BH 2 and AlH 2 (where substitution by -BH 2 reduces the B-F BDE by 31.0 kJ mol −1 compared with the -AlH 2 substituted molecule), it can be seen that for a given group (i.e., groups [14][15][16][17], substitution by elements belonging to the third period give rise to B-F BDEs that are smaller than those obtained in the case of substituents belonging to the second period. The following BDE reductions are noted in the case of each group: 29.2 (Group 14), 20.8 (Group 15), 29.7 (Group 16), and 20.9 kJ mol −1 (Group 17).…”
Section: Effect Of Substituents On the Strength Of B-f Bonds Toward H...mentioning
confidence: 99%
“…From the perspective of its reaction in the gas phase, representative examples of such studies include its reaction with (i) catecholate and related anions [2], (ii) the gas phase ion chemistry of BF 3 /CH 4 mixtures [3], and (iii) the reaction of ammonia and methylamine [4,5]. From the perspective of the reactions of BF 3 in solution (where it is often used in the form of its etherate adduct), it has been shown to play a role in facilitating various polymerization reactions [6][7][8], dehydration reactions of alcohols [9,10], esterification reactions [11][12][13], alkylation reactions [14,15], as well as the synthesis of syn-fluorohydrins from epoxides [16]. It has also been reported that triplet diphenylcarbene could be inserted into the B-F bond of BF 3 [17].…”
Section: Introductionmentioning
confidence: 99%